Recovery of rebaudioside A from stevia rebaudiana (bertoni) extracts using two different purification techniques - Nur Wasilah, Abdul Wahid (2018)
Stevia is a low calories sweetener extracted from the leaves of stevia rebaudiana (Bertoni). Two main compounds responsible for the sweet taste of stevia are stevioside and rebaudioside A (Reb A). Reb A can be considered as the best part of stevia leaves because it is sweeter than stevioside and it has no bitter aftertaste. However, Reb A is very difficult to be separated from other steviol glycosides such as stevioside and rebaudioside C (Reb C) because the chemical structures of stevioside, Reb A, and Reb C are very similar. The objective of this study is to identify the best method that will produce a high yield and purity of Reb A from crude stevia extract. Two types of purification methods were studied in these researches which are liquid-liquid extraction (LLE) using diethyl ether and butanol and adsorption using activated charcoal. Various parameters were carried out such as the ratio of diethyl ether and stevia extract, the percentages of activated charcoal and the extraction stages. The quantification of Reb A was determined by analytical high-performance liquid chromatography (HPLC) using Eclipse Plus C18 (250 × 4.6 mm I.D., 5 μm) column. In this study, LLE was found to be the best purification method because it can recover up to 0.29% of Reb A compared to adsorption method which only can recover 0.01% of Reb A. The analysis showed that the highest yield and purity was obtained at material ratio 1:2 and the extraction needs to be repeated for 3 times in order to recover maximum amount of Reb A. As a conclusion, LLE is the best purification method for recovery of Reb A from stevia extracts.